Seed yield and quality attributes in bottle gourd (Lagenaria siceraria) as influenced by position of seed in fruit - SHARMA, RAJESH KUMAR; TOMAR, B S; JAIN, S K; NEHRA, MAMTA (The Indian Journal of Agricultural Sciences, 2017)
An experiment was conducted at the research field of Seed Production Unit, IARI during kharif 2014-15 to find out the effect of seed position in fruit on the seed yield and quality in bottle gourd (Lagenaria siceraria Mol. Standl.) cv. Pusa Naveen and laboratory observations were carried out at Division of Seed Science and Technology, IARI, New Delhi for seed quality attributes. The results revealed that among the three segments of fruit, viz. stylar, middle and peduncular, the seed extracted from the middle segment of fruit significantly contributed to total number of seed (333.76), filled seed (294.65), seed weight (47.22 g), embryo weight (8.56 mg), germination (95.10%), seedling length (43.24 cm), seedling dry weight (6.98 mg), vigour index I and II (4118.90 and 66.48) followed by stylar segment (251.01, 215.78, 34.13 g, 7.51 mg, 89.6%, 37.81 cm, 5.65 mg, 3397.9 and 50.79 respectively) and lowest values (169.93, 133.28, 20.58 g, 7.15 mg, 83.1%, 30.45 cm, 5.16 mg, 2536.1 and 42.97 respectively) were recorded for peduncular portion. A non-significant difference was noted among the three segments with regard to unfilled seed and 100 seed weight but highest value observed in middle portion. Thus, the seed obtained from middle andstylar segments of fruit were superior in quality than peduncular portion for obtaining high quantity of quality seeds.